1980
DOI: 10.1161/01.cir.62.3.522
|View full text |Cite
|
Sign up to set email alerts
|

Five-year follow-up of maximal treadmill stress test in asymptomatic men and women.

Abstract: A five-year follow-up of 888 asymptomatic men and women without known coronary heart disease (CHD) who had a maximal treadmill stress test (MTST) revealed a CHD incidence of 1.1% per year. In women, exercise duration of 3 minutes or less by the Ellestad protocol correlated with subsequent development of CHD (p less than 0.001), although abnormal ST-segment and R-wave responses did not. In men 40 years of age or younger, the MTST did not correlate with subsequent CHD. In men older than 40 years, ischemic ST res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0
1

Year Published

1983
1983
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(17 citation statements)
references
References 19 publications
1
15
0
1
Order By: Relevance
“…3 Although there is evidence that the development of an ischemic ECG response at low workloads of testing among asymptomatic men is associated with a higher relative risk of future events such as angina pectoris, MI, and sudden death, the absolute risk of cardiac events in these populations remains low. 64 A study using the Ellestad protocol in asymptomatic men and women with known CAD 65 found that ECG ischemic changes and an exercise duration Յ5 minutes correlated with subsequent events in men Ͼ40 years but concluded the exercise ECG had limited value in women and in men Յ40 years. A recent study in 6100 asymptomatic men who were free of clinically detectable cardiovascular disease revealed that the occurrence of frequent premature ventricular depolarizations during exercise testing was associated with a long-term (25 year) increase in the risk of death from cardiovascular causes; no significant increase in shorter term risk was reported.…”
Section: Asymptomatic Subjectsmentioning
confidence: 99%
“…3 Although there is evidence that the development of an ischemic ECG response at low workloads of testing among asymptomatic men is associated with a higher relative risk of future events such as angina pectoris, MI, and sudden death, the absolute risk of cardiac events in these populations remains low. 64 A study using the Ellestad protocol in asymptomatic men and women with known CAD 65 found that ECG ischemic changes and an exercise duration Յ5 minutes correlated with subsequent events in men Ͼ40 years but concluded the exercise ECG had limited value in women and in men Յ40 years. A recent study in 6100 asymptomatic men who were free of clinically detectable cardiovascular disease revealed that the occurrence of frequent premature ventricular depolarizations during exercise testing was associated with a long-term (25 year) increase in the risk of death from cardiovascular causes; no significant increase in shorter term risk was reported.…”
Section: Asymptomatic Subjectsmentioning
confidence: 99%
“…Similarities in cardiovascular structure and function, combined with previous similarities in vascular structure and function [3739], suggest that the differences in cardiovascular disease are rooted outside of cardiovascular physiology and genetics, as previously suggested [40,41]. Alternatively, while ethnic differences in resting cardiovascular dynamics were not identified, ethnic differences may be more apparent when evaluating ECG during maximal or near-maximal exercise stress tests which are prognostic for identifying cardiac arrhythmias and abnormalities among asymptomatic individuals with underlying cardiovascular disease [42]. …”
Section: Discussionmentioning
confidence: 78%
“…1-13,20 -22 Numerous studies have demonstrated that asymptomatic subjects with exercise-induced ischemic ST-segment depression, defined by Ն1 mm horizontal or downsloping ST depression, have a several-fold higher risk of future CE than those with negative exercise ECGs. [1][2][3][4][5][6][7][8][9][10][11][12][13] For many years, exercise-induced ST-segment depression Ͻ1 mm has generally been considered negative or nondiagnostic for ischemia, on the basis of the observation that these lesser ST-segment shifts increase sensitivity for angiographic CHD, but with substantial drops in specificity. In 100 Another study in symptomatic patients who underwent angiography found that the specificity and sensitivity for 0.5-mm ST depression were 83% and 63% compared with 100% and 35%, respectively, for 1-mm horizontal or downsloping ST-segment depression.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the availability of newer methods, it remains a first-line diagnostic test for CHD. Numerous studies, [1][2][3][4][5][6][7][8][9][10][11][12][13] including two from our laboratory, 1,2 have shown that a horizontal or downsloping ST-segment depression Ն1 mm in response to exercise is a powerful harbinger for future coronary events (CE), ie, angina pectoris, myocardial infarction (MI), or sudden cardiac death, in an apparently healthy population, independent of conventional risk factors. In symptomatic populations, lesser ST-segment shifts defined by horizontal depression Ͻ1 mm or slowly upsloping ST segments have also demonstrated diagnostic 14,15,16 and prognostic significance.…”
mentioning
confidence: 99%